Technology manufacturing Ghazi oven and sessile cost of production of ceramic (Al-Academy, 2017)
The ceramic work of the business that was stationed with the history of its evolution of man on earth, and this gives him a linking formula and the reality of life, including asking as inherited civilized . Operation creativity over several stages and developments have helped in the formation of human hands, including a reflection on productions are large and diverse.To search for new horizons in ceramic art began to form new technologies outside the traditional frameworks ,devoted technical and scientific expertise and access to an advanced stage in porcelain from technical and aesthetic point of view the field, shall be deemed to contemporary ceramic civilized idea of ​​Modernism from the ceramic work can in no way be independently from the effects of the current environment and circumstances. Iraqi pottery devoted material saved by the researchers a starting point of need based on the times of the establishment of Ceramic Art at less cost and easier techniques and advantageous material, and get to know the merits in the field of furnaces in Iraq and the formation of a technical subject to its effect on various factors led to the accomplished according to certain vision, it can be comes the question of the research problem the following: Is possible to manufacture furnace for the production of ceramic works and the cost of gas and low-lying?Current search included four chapters included chapter (research problem - the importance of research and the need to – research object : is the detection techniques in the manufacture of ceramic gas ovens and low cost - the limits of research - to identify and define the terminology. The search included the second chapter (theoretical framework), which included (historical introduction about the history of furnaces - furnace types - burn.The third chapter included the research methodology (experimental method). The fourth chapter has been included on the findings and recommendations, and then the list of sources.